Narrativas de experiências com a pesquisa como princípio educativo - da educação infantil à educação profissional técnica de nível médio - Silva, Carla Melo da (2021)
This investigation presents the narratives of teachers from Kindergarten to the Final Years of Elementary School; teachers and students of technical professional education in Chemistry who share their experiences with research as an educational principle. The focus of this study was the Municipal Network of Novo Hamburgo – RS and the Liberato Salzano Vieira da Cunha Foundation, in the same city. The question that guided this investigation was: How are the formative and constitutional relationships of the subjects established in the experiences in municipal schools in Novo Hamburgo and the Liberato Salzano Vieira da Cunha Foundation, considering the assumptions of research as an educational principle, based on the narratives of teachers, students, and managers? The general objective of this research was to understand the narratives of teachers, students, and managers about the establishment of the formative and constitutional relationships of subjects in experiences in municipal schools in Novo Hamburgo and the Liberato Salzano Vieira da Cunha Foundation, considering the assumptions of research as an educational principle. The research is characterized as qualitative and is of the narrative research type with the approach of professional life experience. The differences between narrative research, narrative, narrative interview, and narrative analysis are presented in this study. The study had fourteen participants, whose narratives were first analyzed with the narrative structure proposed by the sociolinguist William Labov and, later, a hermeneutic analysis was carried out based on the ideas of the philosopher Hans-George Gadamer, in which a hermeneutic exercise of understanding was carried out the meanings of the narratives, by identifying in them the answers to the research problem. Asking is relevant to hermeneutic understanding since to understand what is the aid we need to answer a question. This made it possible to understand the significant knowledge strengthened by research as an educational principle; the formation and constitution of the participants involved in the research; everyday situations in the classroom that enhance research as an educational principle; and the theoretical assumptions used by teachers for teaching with research as an educational principle. These understandings led to the conclusion that in both study environments, although research actions occur as an educational principle, which contributes to investigative training and the teaching and learning process, there is no theoretical approach explicitly assumed in all situations, consisting of the practice in a deductive mode. This points to the need for continuous training actions, involving frequent moments of theorizing on the part of teachers for the understanding and assumption that theory follows practice, but it is necessary to build awareness concerning this.